Efektivitas Program TPA Efektivitas Program TPA terhadap Kemampuan Membaca Al-Qur’an Anak-Anak di Masjid Taqwa Parak Juar : Efektivitas Program TPA terhadap Kemampuan Membaca Al-Qur’an Anak-Anak di Masjid Taqwa Parak Juar - Gusrina Fadhila; julita_putri putri; Math Rafin (Makkareso: Riset Pengabdian Masyarakat, 2026)
This study investigates the effectiveness of the Taman Pendidikan Al-Qur’an (TPA) program on the Qur’anic reading ability of children at Masjid Taqwa Parak Juar. The research aims to identify the extent to which the program improves students’ proficiency in recognizing letters, applying tajwid rules, and reading fluently. A quantitative descriptive approach was employed, involving pre- and post-assessments of participants’ reading skills as well as structured observations during the learning process. The sample consisted of children aged 6–12 years who actively attended the TPA sessions. Data were analyzed using paired sample t-tests to determine significant differences before and after program participation. The findings indicate a marked improvement in accuracy, fluency, and tajwid application among participants, with statistically significant results (p < 0.05). This suggests that the TPA program plays a crucial role in enhancing Qur’anic literacy at the community level. Furthermore, the study highlights the importance of structured teaching methods, trained instructors, and consistent practice in achieving optimal learning outcomes for young Qur’an learners. Keywords: TPA program, Qur’anic literacy, tajwid, reading fluency, children]